A model for current source inverter fed induction motor / Piush Kumar and Vineeta Agarwal - Kumar, Piush; Agarwal, Vineeta (UiTM Press, 2008)
A model has been developed for self-commutated current source inverter (SCCSI) fed induction motor in synchronously rotating d-q reference frame using proportional regulators in speed and current loops. The steady-state parameters and slip regulator characteristics of the drive are determined experimentally. Transient as well as steady state performance is obtained by developing a computer programme in MATLAB. The analysis has been carried out for the different values of the speed and current controller parameters. It has been found that with an increase in speed controller parameter Kps, the stator current as well as torque developed by the motor both reduces but the transient time to reach the steady state condition increases. There is a large drop in dc link current with a change in speed. However, there is no effect on current and torque when current controller parameter Kpi changes, But, the stator voltage increases rapidly with an increase in Kpi.. For the selected motor, controller parameter are obtained such that Kps 20 and Kpi 0.6.